2021
DOI: 10.3389/fvets.2021.684295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Guanidinoacetic Acid on the Feed Efficiency, Blood Measures, and Meat Quality of Jinjiang Bulls

Abstract: An experiment was conducted to determine the effects of supplementing the diet of Jinjiang bulls with guanidinoacetic acid (GAA) on their feed efficiency [feed efficiency were evaluated with feedlot average daily gain (ADG), average daily feed intake (ADFI), and feed-to-gain ratio (F:G)], blood measures, and meat quality. Forty-five Jinjiang bulls (24 ± 3 months old and 350.15 ± 30.39 kg by weight) were randomly distributed among five experimental groups (each n = 9) and each group was randomly fed with one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
(126 reference statements)
3
10
0
Order By: Relevance
“…Supplementation of GAA in Tibetan pigs beneficially increased the SOD activity and decreased the MDA content in LT, suggesting that GAA enhanced the antioxidant capacity of LT. These findings are consistent with those presented by Li et al (30), who reported an increase in serum SOD, glutathione, and glutathione/oxidized glutathione ratio in the GAA group compared to the control group. GAA supplementation in pig diets significantly reduced the muscle MDA content and increased the GSH-Px and SOD activities (31).…”
Section: Discussionsupporting
confidence: 93%
“…Supplementation of GAA in Tibetan pigs beneficially increased the SOD activity and decreased the MDA content in LT, suggesting that GAA enhanced the antioxidant capacity of LT. These findings are consistent with those presented by Li et al (30), who reported an increase in serum SOD, glutathione, and glutathione/oxidized glutathione ratio in the GAA group compared to the control group. GAA supplementation in pig diets significantly reduced the muscle MDA content and increased the GSH-Px and SOD activities (31).…”
Section: Discussionsupporting
confidence: 93%
“…This was consistent with previously reported about Jinjiang bulls and Angus bulls. Li et al ( 26 ) and Li et al ( 27 ) found that the DMI of Jinjiang bulls and Angus bulls increased with GAA addition. However, the findings of the present study contrasted with the results of a previous study with uncoated GAA at Xinjiang Agricultural University of China ( 28 ), in which adding GAA without rumen protection treatment in TMR significantly decreased the DMI of lambs but the ADG and F: G were similar.…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies, uncoated GAA was applied as feed additive, and it was found as an improvement of growth performance and feed efficiency in pigs, broiler chickens, and bulls ( 24 26 ). However, there was little information available concerning the forage type and GAA addition on Han lamb performance.…”
Section: Discussionmentioning
confidence: 99%
“…The DMI was unchanged with GAA addition, and was in agreement with the findings reported in bulls. 9,24 Likewise, Speer reported that the DMI was not affected with a ruminal infusion of 10 or 20 g day −1 GAA in steers. 10 However, Li et al 8 observed that the DMI of bulls linearly increased when supplementing the same level of GAA as that in the present study.…”
Section: Discussionmentioning
confidence: 99%